Ground Handling Operations Management: An Agent-Based Modelling Approach (Global Journal of Science Frontier Research, 2018)
This work addresses the resource allocation-routing problem in the aircraft Ground Handling (GH) context. This problem is classified as one of the challenges that most of the ground-handling operators face nowadays. It consists of allocating a number of resources including workers and vehicles to aircraft of different service requirements and specifications. The allocation deals with the assignment of m teams of n skilled workers to k special purpose vehicles to serve i aircraft on the air-side area, while the routing is to determine the optimal route used by a group of workers integrated with vehicles when serving one or more aircraft. Both the allocation and routing tasks are affected by a number of constraints including different aircraft types and sizes, different aircraft service times, and various GH operation details based on flight types.
Keywords: resource allocation; routing; aircraft; ground handling operations; autonomous system; algorithms; simulation